S-531011, a Novel Anti-Human CCR8 Antibody, Induces Potent Antitumor Responses through Depletion of Tumor-Infiltrating CCR8-Expressing Regulatory T Cells - Nagira, Yoji; Nagira, Morio; Nagai, Ryohei; Nogami, Wataru; Hirata, Michinari; Ueyama, Azumi; Yoshida, Tetsuya; Yoshikawa, Mai; Shinonome, Satomi; Yoshida, Hiroshi; Haruna, Miya; Miwa, Hiroto; et al. (Molecular cancer therapeutics, 2023)
Although regulatory T cells (Treg) are inhibitory immune cells that are essential for maintaining immune homeostasis, Tregs that infiltrate tumor tissue promote tumor growth by suppressing antitumor immunity. Selective reduction of tumor-infiltrating Tregs is, therefore, expected to activate antitumor immunity without affecting immune homeostasis. We previously reported that selective Treg depletion targeted by a C-C motif chemokine receptor 8 (CCR8) resulted in induction of strong antitumor immunity without any obvious autoimmunity in mouse models. Thus, herein, we developed a novel humanized anti-CCR8 monoclonal antibody, S-531011, aimed as a cancer immunotherapy strategy for patients with cancer. S-531011 exclusively recognized human CCR8 among all chemokine receptors and showed potent antibody-dependent cell-mediated cytotoxicity activity toward CCR8+ cells and neutralization activity against CCR8-mediated signaling. We observed that S-531011 reduced tumor-infiltrating CCR8+ Tregs and induced potent antitumor activity in a tumor-bearing human-CCR8 knock-in mouse model. Moreover, combination therapy with S-531011 and anti-mouse programmed cell death 1 (PD-1) antibody strongly suppressed tumor growth compared with anti–PD-1 antibody alone with no observable adverse effects. S-531011 also depleted human tumor-infiltrating Tregs, but not Tregs derived from human peripheral blood mononuclear cells. These results suggest that S-531011 is a promising drug for inducing antitumor immunity without severe side effects in the clinical setting.